Forest Cover Dynamics in Nilgiri Biosphere Reserve - Bisht, M. S. (Indian Forester, 1999)
The destruction and degradation of forests is now recognised as one of the greatest environmental threats - and tragedies - of all times. It is tragedy manifested in the loss of species, the rapid wiping out of the richest sources of biodiversity, disruption of the water cycle and of climatic balance. The analysis provided in the paper shows that in Nilgiri Biosphere Reserve area, the forest cover has increased showing a positive trend, which needs to be maintained.